Connecting blog, Twitter and Facebook use with gaps in knowledge and participation (Communication & Society, 2014)
Although they share a similar ‘social media’ tag, blogs, micro-blog sites like Twitter, and social networking sites (SNS) like Facebook are distinctive in their relationships with political engagement. This paper examined the impact of the use of the three media on the gaps in political knowledge and participation between the more and less educated people. In the results, Facebook use interacted positively with education in predicting civic and issue knowledge. The gap of offline participation was larger among heavy Twitter users than among light users. Overall, findings imply that social media amplify or reinforce inequality of political engagement.